2020
DOI: 10.21037/jtd-20-286
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of robot-assisted thoracoscopic surgery for posterior mediastinal neurogenic tumors

Abstract: Background: Robot-assisted thoracic surgery (RATS) has an increasing usage throughout the world. This retrospective cohort study aimed to objectively compare the surgical results between video-assisted thoracic surgery (VATS) and RATS in posterior mediastinal neurogenic tumors (PMNT). Methods: We retrospectively reviewed the clinical data of 130 patients diagnosed with posterior mediastinal neurogenic tumor between 2015 and 2018. Magnetic resonance imaging (MRI) or enhanced computed tomography scan (CT-scan) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…The possible rationales for the superior performance of RATS over VATS in terms of surgical blood loss can be elucidated as follows: firstly, RATS offers 3D visualizations with 10x magnified images and superior image quality, facilitating the recognition of different structures during surgery. Secondly, RATS permits freely articulated movement of its robotic arms and seven degrees of operational dexterity, enabling more exact dissection, reducing the risk of nerve and artery damage, and providing surgeons with a secure and comfortable setup 17 .Thirdly, CO2 insufflation in robotic surgery provided adequate working space that can hardly be obtained. When the tumor size is small, VATS can provide a sufficiently good operating environment, but when the tumor size exceeds a certain threshold, the advantageous conditions offered by RATS can demonstrate its value.…”
Section: Discussionmentioning
confidence: 99%
“…The possible rationales for the superior performance of RATS over VATS in terms of surgical blood loss can be elucidated as follows: firstly, RATS offers 3D visualizations with 10x magnified images and superior image quality, facilitating the recognition of different structures during surgery. Secondly, RATS permits freely articulated movement of its robotic arms and seven degrees of operational dexterity, enabling more exact dissection, reducing the risk of nerve and artery damage, and providing surgeons with a secure and comfortable setup 17 .Thirdly, CO2 insufflation in robotic surgery provided adequate working space that can hardly be obtained. When the tumor size is small, VATS can provide a sufficiently good operating environment, but when the tumor size exceeds a certain threshold, the advantageous conditions offered by RATS can demonstrate its value.…”
Section: Discussionmentioning
confidence: 99%
“…As a common disease in thoracic surgery, the surgical treatment of mediastinal lesions has undergone signi cant changes in recent years, mainly due to the popularity of minimally invasive surgery and the rapid development of energy platforms. Compared with the thoracoscopic surgery, robotic surgical systems have better visualization and more exible instrumentation, so they have also been widely used in the treatment of mediastinal tumors in recent years [9,10]. Two main types of energy instruments in current robotic surgical systems are MF and EH.…”
Section: Discussionmentioning
confidence: 99%
“…A single-institutional retrospective study of 130 patients with a posterior mediastinal neurogenic tumor resected by RATS ( n = 58) or by VATS ( N = 72) showed that RATS approach was significantly associated with a shorter intraoperative blood loss (85.8 mL versus 95.3 mL; P = 0.040) and a shorter postoperative hospital stay (2.2 days versus 2.4 days; P = 0.040). Concerning the incidence of postoperative complications, there was no significant difference between RATS approach and VATS approach (5.2 vs. 9.7%) [ 4 ]. A retrospective analysis of nation-wide database, which included 856 patients who underwent a minimally invasive surgery (RATS or VATS) for a mediastinal tumor in the United States, also showed a shorter hospital stay in the RATS group (3.8 days versus 4.3 days; P = 0.01).…”
Section: Conclusion and Discussionmentioning
confidence: 99%